Chlamydial Pgp3 Seropositivity and Population-Attributable Fraction Among Women With Tubal Factor Infertility. Issue 8 (31st August 2022) - Anyalechi, Gloria E.; Hong, Jaeyoung; Kirkcaldy, Robert D.; Wiesenfeld, Harold C.; Horner, Paddy; Wills, Gillian S.; McClure, Myra O.; Hammond, Karen R.; Haggerty, Catherine L.; Kissin, Dmitry M.; Hook, Edward W.; Steinkampf, Michael P.; et al.
Abstract : Chlamydia trachomatis Pgp3 seropositivity is associated with tubal factor infertility in non-Black women without endometriosis. Past chlamydial infection may account for tubal factor infertility in 20% of these women. Abstract : Background: Chlamydial infection is associated with tubal factor infertility (TFI); however, assessment of prior chlamydial infection and TFI is imperfect. We previously evaluated a combination of serological assays for association with TFI. We now describe the chlamydial contribution to TFI using a newer Chlamydia trachomatis Pgp3-enhanced serological (Pgp3) assay. Methods: In our case-control study of women 19 to 42 years old with hysterosalpingogram-diagnosed TFI (cases) and non-TFI (controls) in 2 US infertility clinics, we assessed possible associations and effect modifiers between Pgp3 seropositivity and TFI using adjusted odds ratios with 95% confidence intervals (CIs) stratified by race. We then estimated the adjusted chlamydia population-attributable fraction with 95% CI of TFI. Results: All Black (n = 107) and 618 of 620 non-Black women had Pgp3 results. Pgp3 seropositivity was 25.9% (95% CI, 19.3%–33.8%) for non-Black cases, 15.2% (95% CI, 12.3%–18.7%) for non-Black controls, 66.0% (95% CI, 51.7%–77.8%) for Black cases, and 71.7% (95% CI, 59.2%–81.5%) for Black controls. Among 476 non-Black women without endometriosis (n = 476), Pgp3 was associated with TFI (adjusted odds ratio, 2.6 [95% CI, 1.5–4.4]), adjusting for clinic, age, and income; chlamydia TFI-adjusted population-attributable fraction was 19.8% (95% CI, 7.7%–32.2%) in these women. Pgp3 positivity was not associated with TFI among non-Black women with endometriosis or among Black women (regardless of endometriosis). Conclusions: Among non-Black infertile women without endometriosis in these clinics, 20% of TFI was attributed to chlamydia. Better biomarkers are needed to estimate chlamydia TFI PAF, especially in Black women.